Effect of stabilized laterite on California bearing ratio (CBR) and unconfined compressive strength (UCS) [electronic resource] - Zuraida Zainudin, 1988-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2013